2020
DOI: 10.1108/bij-07-2019-0304
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effectiveness of maintenance and quality management strategies in Indian manufacturing enterprises

Abstract: PurposeThe purpose of the paper is to examine the impact of human-related support practices, total productive maintenance (TPM) practices, and total quality management (TQM) practices on manufacturing performance parameters and their inter-relationship.Design/methodology/approachA research project was carried out in 94 Indian manufacturing companies, using the questionnaire method. The survey data was drawn from 169 respondents working in these companies. In this paper, the impact of TPM and TQM practices on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 104 publications
(184 reference statements)
2
19
0
1
Order By: Relevance
“…Seth et al (2005) studied 19 models on service quality used for measuring consumer E-healthcare services using the 5Qs model satisfaction and observed that different models have developed with different types of services and have continuously evolved with the changing situations. Total quality is a significant methodology for improvements in quality and outcome to meet or surpass customer expectations (Sahoo, 2020). It is an approach to plan, organize and direct the whole thing in the establishments, which measures the general quality aspects adopted to achieve excellence (Kaur et al, 2013;Sahoo, 2020;Sinha et al, 2016).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Seth et al (2005) studied 19 models on service quality used for measuring consumer E-healthcare services using the 5Qs model satisfaction and observed that different models have developed with different types of services and have continuously evolved with the changing situations. Total quality is a significant methodology for improvements in quality and outcome to meet or surpass customer expectations (Sahoo, 2020). It is an approach to plan, organize and direct the whole thing in the establishments, which measures the general quality aspects adopted to achieve excellence (Kaur et al, 2013;Sahoo, 2020;Sinha et al, 2016).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Total quality is a significant methodology for improvements in quality and outcome to meet or surpass customer expectations (Sahoo, 2020). It is an approach to plan, organize and direct the whole thing in the establishments, which measures the general quality aspects adopted to achieve excellence (Kaur et al, 2013;Sahoo, 2020;Sinha et al, 2016). Total quality represents a set of tools, procedures and actions used to reduce nonconformities from service delivery systems (Dubey et al, 2018) along with providing prospects to learn and improve through problemsolving exercises.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Organisations usually use excellence models to monitor and improve performance because the models are based on TQM principles and are considered a way of planning, organising and directing everything in the organisations to attain excellence (Sahoo, 2020). TQM aims to improve processes, products and operations; meet customer expectations and maximise market share, productivity and operations performance; reduce the cost of operations; utilise quality exploration and exploitation; and achieve a competitive advantage to become world class (Sweis et al , 2015; Sharma and Modgil, 2015, 2019; Modgil and Sharma, 2016; Cho et al , 2017; Kumar et al , 2018; Dubey et al , 2018; Cho and Linderman, 2019; Georgiev and Ohtaki, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The philosophy of integrated manufacturing promotes the idea that manufacturing technologies can work together to boost the production output (Furlan et al, 2011;Khanchanapong et al, 2014;Dubey and Singh, 2015;Sahoo, 2020). Some studies suggest that, although Lean and TQM work separately, their combination may yield synergies that lead to further operational improvements (Belekoukias et al, 2014;Pont et al, 2008;Pramod et al, 2006;Singh and Ahuja, 2015).…”
Section: Operational Practices and Competitive Strategiesmentioning
confidence: 99%
“…In light of these divergent views, an objective of this research review is to investigate the gaps in performance contribution between the stand-alone and combined interaction of lean and TQM practices. Therefore, based upon the above discussion and growing recognition of future studies to investigate the bundled approach of lean and TQM practices (Belekoukias et al, 2014;Chiarini and Baccarani, 2016;Ho, 2010a;Ho, 2010b;Jayaram et al, 2014;Modgil and Sharma, 2016;Sahoo, 2020), the researcher postulates the following hypothesis:…”
Section: Operational Practices and Competitive Strategiesmentioning
confidence: 99%